Hubungan Kadar HbA1c dengan Kadar Kreatinin Darah pada Pasien Diabetes Melitus Tipe 2 di RSUD ODSK Provinsi Sulawesi Utara - Aurelia Putri Valencia Gawendaleng; Diana Shintawati Purwanto; Murniati Tiho (Pusat riset dan Inovasi Nasional, 2026)
Diabetes mellitus (DM) is a global health problem characterized by increased blood glucose levels. Type 2 diabetes mellitus (T2DM) accounts for 90-95% of all diabetes cases and is characterized by insulin resistance. Persistent hyperglycemia in patients with T2DM increases the risk of various complications, including renal dysfunction. Therefore, monitoring HbA1c levels is important for assessing long-term glycemic control and preventing complications, one of which is impaired kidney function that can be detected through increased blood creatinine levels. To analyze the relationship between HbA1c levels and blood creatinine levels in type 2 diabetes mellitus patients at RSUD ODSK North Sulawesi Province. This study used an observational analytic design with a cross-sectional approach. This study was retrospective using secondary data in the form of medical record data for the period February 2024-August 2025. This study used a total sampling method with 71 patients who met the inclusion criteria. The findings showed that the majority of patients had HbA1c levels >6,5%, while most blood creatinine levels were within the normal range. Based on the results of the Spearman-Rank correlation test, a significance value of 0.040 (p-value <0.05) was obtained. There is a significant relationship between HbA1c levels and blood creatinine levels, with a negative correlation strength in patients with type 2 diabetes mellitus at RSUD ODSK North Sulawesi Province.